Efektifitas Desain Kemasan Thung Cha Terhadap Ergonomi Konsumen - Ellen Moza Liguna (Universitas Katolik Soegijapranata, Semarang, 2018)
The development of the more advanced era, the more creativity that is created by someoneto improve the quality of a product. Especially creativity in packaging design. With thecreativity of packaging design, very helpful in a selling point in doing business. Manyentrepreneurs who sell fast drinks like tea, pop ice, juice, etc. with the use of cup packaging.The world of competition is still running, so it is necessary to find something different withcreative ideas. One of them is Thai Tea beverage product with Thung Cha brand. Thai Teais a tea drink from Thailand, which is currently popular and many people are opening thisbusiness. Thung Cha therefore makes a different packaging design from the others, namelythe packaging of Zip Bag. The packaging is shaped like a pouch or a flip pouch on the top.Usually this packaging is used to package snacks or snacks. From the packaging of thispouch type of drink, makes the author interested to examine why drinks are packed usingZip Bag packaging.